Penerapan Ilmu Ushul Fiqh Dalam Penetapan Istinbath Hukum Produk Halal di Indonesia - Badrud Tamam; Saiban, Kasuwi; Munir, Misbahul (DPPM Universitas Pelita Bangsa, 2022)
The science of Ushul Fiqh is a discipline that is very urgent for Islamic law experts in determining halal products in Indonesia, because with this knowledge, a mujtahid or Islamic law expert, can find it easy to find out contemporary economic laws that are not contained the sharih texts in the Qur’an and Al-Hadits. In addition, the Science of Ushul Fiqh can also make it easier to understand and master the problems of furu’iyah or fiqhiyah which continue to develop at the rate of development of the times, situations and conditions, and they are all countless. The science of ushul fiqh in the field of economics can be a solution in justifying and providing legal legitimacy to all movements of economic activity in various fields of transactions (muamalah), which if all of this is in accordance with the halal principle that is, does not conflict with the texts and maqoshid al-syariah.